The relevance of antral follicle count (AFC) as a marker of ovarian reserve in normal and infertile women in a tertiary care centre in Central India - Nayak, Prasanta K.; Mukherjee, Chandrima; Mitra, Subarna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the present study was to establish the role of AFC as a marker of ovarian reserve in fertility-proven and in sub-fertile Indian women, and to establish the baseline cut-off AFC values for Indian women. Methods: This is an Observational Case-Control type of study. Test subjects (n=30, age range 20-35 years) were selected randomly from all the women coming to our Out-Patient Department with Primary Infertility. Healthy female volunteers (n=30, age range 20-35years) were recruited from the local population. Statistics: Student t test was applied to compare the mean Antral Follicle count between the case and control group. Pearson correlation test was applied to assess the correlation between age and AFC for case and control group. Results: The results of the study show that there is a significant difference between the number of antral follicles between fertile and infertile women (p < 0.001). The baseline cut-off for successful pregnancy was established as an AFC of 12. There exists negative correlation (r = -0.249) between age and AFC case group indicating as the age increases AFC decreases. Conclusions: The findings from this study help in strengthening the idea that AFC serves as a marker for ovarian reserve. Our observation indicates that the number of antral follicles is lower in the subfertile patients as compared to the fertile group (in all age groups), in view of the significantly lower median AFC in women of the former group (P < 0.001).